Clinical Manifestations of Type 1 Gaucher Disease - SALEHPOUR, Shadab (Iranian Journal of Child Neurology, 2012)
How to Cite this Article: Salehpour Sh. Clinical Manifestations of Type 1 Gaucher Disease. Iran J Child Neurol Autumn 2012; 6:4 (suppl. 1):13-14. pls see PDF. References 1. Beutler E, Grabowski GA. Gaucher disease. In: Metabolic and molecular bases of inherited disease, Scriver CR, Beaudet AL, Sly WS, Valle D (Eds), McGraw-Hill, New York 2001: 3635. 2. Cox TM, Schofield JP. Gaucher’s disease: clinical features and natural history. Baillieres Clin Haematol. 1997 Dec;10(4):657-89.